Efektivitas Pendidikan Kesehatan Menggunakan Media Video Animasi Terhadap Pengetahuan dan Perilaku SADARI Remaja Putri di SMAN 1 Kapuas Hilir: The Effectiveness of Health Education Using Animation Video Media on the Knowledge and Behavior of BSE of Adolescent Girls at SMAN 1 Kapuas Hilir - Sukriani, Wahidah; Yuniasi, Rima; Eline Charla Sabatina (Jurnal Forum Kesehatan : Media Publikasi Kesehatan Ilmiah, 2025)
Currently, breast cancer does not only vulnerable ages but also young ages, so adolencents (13-20 years) need to do BSE regularly to prevent and detect it early. Health education is on of the efforts to make promotive behaviour change. One of the health education is BSE. BSE is one way that is effective, easy, an can be done by every woman to maintain and check breast health independently. Research Objective To determine the effectiveness of health education using animation video media on the knowledge and behavior of adolescent girls at SMAN 1 Kapuas Hilir. The design of this study was quasi-experimental with pretest posttest Nonequivalent Control Group Design, namely the intervention group in the form of animated videos and the control group in the form of videos. The results showed a significant difference in value (p-value) before and after being given helath education with animated video media and video slide shows, which animated to 0.00 which indicates that the p- value is smaller than 0.05. There is a significant difference between before and after treatment, both in the animated video and slide show groups for the knowledge and behaviour of BSE adolescent girls SMAN 1 Kapuas Hilir.